2007
DOI: 10.1007/s11242-006-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Flow of low pressure gas through dual-porosity media

Abstract: Using the theory of homogenization we derive macroscopic models for describing flow of gas at low pressure in dual-porosity media. The case of a fractured porous medium is under consideration for the study, and the existence of a representative elementary volume that consists of open connected fractures surrounded by porous matrix blocks is assumed. The local flow is governed by either Klinkenberg's law or Knudsen's diffusion law in the matrix while either a non-slip flow or a slip flow occurs in the fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Rarefaction effects are therefore neglected. However, it has been shown that these effects do not change the form of the macroscopic isothermal acoustic description in single 26 and double 27 porosity materials but the way the effective quantities are calculated. To model the material as a homogenous equivalent fluid, the separation of scales assumption should be satisfied, e.g., e ¼ l p =L ( 1 and e 0 ¼ l m =l p ( 1.…”
Section: Theorymentioning
confidence: 99%
“…Rarefaction effects are therefore neglected. However, it has been shown that these effects do not change the form of the macroscopic isothermal acoustic description in single 26 and double 27 porosity materials but the way the effective quantities are calculated. To model the material as a homogenous equivalent fluid, the separation of scales assumption should be satisfied, e.g., e ¼ l p =L ( 1 and e 0 ¼ l m =l p ( 1.…”
Section: Theorymentioning
confidence: 99%
“…For pores smaller than the molecular mean free path the Knudsen number becomes large and the dominant transport mechanism is Knudsen diffusion 9,16 rather than viscous slip flow. It states that the diffusive transport is proportional to the pressure gradient 2,9,16,29 and the filtration velocity is given by:…”
Section: A Sound Propagation In Single Porosity Materials Accountingmentioning
confidence: 99%
“…Diagram of the scales of a double porosity material (adapted from Ref 26 ). The wave equation in a rigid-frame double porosity granular material has the same general form6,7,25,26,29 as that of Eq.(35). However, E and k should be replaced by the dynamic bulk modulus db E and dynamic viscous permeability db k of the double porosity granular material.…”
mentioning
confidence: 99%
“…As it will be seen in §4.3, the result is of crucial importance for the determination of the order of magnitude of the velocity ratio for transient fluid flow in dualporosity media. Several empirical approaches have been made for determining this order of magnitude, but with no clear understanding on the rules which condition the result (Royer and Auriault 1994), (Chastanet et al 2007). Thanks to the above time analysis which suggests to examine the temporal regimes, we are in position to rigorously derive this fundamental result.…”
Section: Order Of Magnitude Of the Flux Ratiomentioning
confidence: 99%